The incidence of non-affective psychotic disorders in Chile between 2005 and 2018: results from a national register of over 30 000 cases. Issue 5 (6th April 2022) - González-Valderrama, Alfonso; Jongsma, Hannah E.; Mena, Cristián; Castañeda, Carmen Paz; Nachar, Rubén; Undurraga, Juan; Crossley, Nicolás; Aceituno, David; Iruretagoyena, Barbara; Gallardo, Carlos; Mondaca, Pilar; Monje, Matías; et al.
Abstract: Background: Evidence suggests the incidence of non-affective psychotic disorders (NAPDs) varies across persons and places, but data from the Global South is scarce. We aimed to estimate the treated incidence of NAPD in Chile, and variance by person, place and time. Methods: We used national register data from Chile including all people, 10–65 years, with the first episode of NAPD ( International Classification of Diseases, Tenth Revision: F20–F29) between 1 January 2005 and 29 August 2018. Denominators were estimated from Chilean National Census data. Our main outcome was treated incidence of NAPD and age group, sex, calendar year and regional-level population density, multidimensional poverty and latitude were exposures of interest. Results: We identified 32 358 NAPD cases [12 136 (39.5%) women; median age-at-first-contact: 24 years (interquartile range 18–39 years)] during 171.1 million person-years [crude incidence: 18.9 per 100 000 person-years; 95% confidence interval (CI) 18.7–19.1]. Multilevel Poisson regression identified a strong age–sex interaction in incidence, with rates peaking in men (57.6 per 100 000 person-years; 95% CI 56.0–59.2) and women (29.5 per 100 000 person-years; 95% CI 28.4–30.7) between 15 and 19 years old. Rates also decreased (non-linearly) over time for women, but not men. We observed a non-linear association with multidimensional poverty and latitude, with the highest rates in the poorest regions and those immediately south of Santiago; no association with regional population density was observed. Conclusion: Our findings inform the aetiology of NAPDs, replicating typical associations with age, sex and multidimensional poverty in a Global South context. The absence of association with population density suggests this risk may be context-dependent.